LA FAMILIA PAPILIONIDAE EN CHILE (LEPIDOPTERA) - Herrera, José; Atria, Juan (Acta Entomológica Chilena, 2022)
The only known species of Papilionidae from Chile, Battus arcliidamas (Boisduval, 1836), is redescribed in this paper. Its distribution in the country and genitalia of both sexes is discussed, as well as its sexual dimorphism, biology and development, host plant (Aristolochia), synonymy, etc. An exhaustive discussion of the published lilerature is also presenled. The ñame Papilio psittaciis Molina 1782, can nol at all be applied to this species, and the Molina ñame ought to be invalidated and declared unrecognizable, since there not exist type (s) of the Molina species and the original description does not permit lo recognize the species.